Marriage of convenience as a strategy of integration and accumulation among Nigerian migrant entrepreneurs in Harare, Zimbabwe. Issue 2 (3rd April 2021) - Mushonga, Rufaro Hamish; Dzingirai, Vupenyu
ABSTRACT: Internal migration is increasing within the African continent, but the processes by which migrants integrate and accumulate in the host community remain bewildering. Using ethnography as a method of enquiry, this article investigates 'marriages of convenience' between Nigerian migrant entrepreneurs and Zimbabwean nationals in Harare, Zimbabwe. It examines how these marriages serve as a strategy to negotiate an 'insider' identity so as to integrate and accumulate (business advancement) among Nigerian migrant entrepreneurs. However, the article also shows how local women are repurposing these relations for their own ends. Thus, these conjugal relationships are therefore represented as transactions that are mutually beneficial. This is an important addition to the body of knowledge on the complexities of South-South migration as it helps us to understand the politics of integration and belonging in the politically and economically troubled host communities.